Dexamethasone-Sparing Regimens with Oral Netupitant and Palonosetron for the Prevention of Emesis Caused by High-Dose Cisplatin: A Randomized Noninferiority Study. (18th June 2021) - Celio, Luigi; Cortinovis, Diego; Cogoni, Alessio Aligi; Cavanna, Luigi; Martelli, Olga; Carnio, Simona; Collovà, Elena; Bertolini, Federica; Petrelli, Fausto; Cassano, Alessandra; Chiari, Rita; Zanelli, Francesca; et al.
Abstract: Background: To reduce the overall exposure to dexamethasone (DEX) in patients receiving cisplatin-based chemotherapy, we evaluated the noninferiority of DEX on day 1, with or without low-dose DEX on days 2 and 3, combined with an oral fixed-dose combination of netupitant and palonosetron (NEPA), compared with the guideline-consistent use of 4-day DEX. Patients and Methods: In this open-label, multicenter study, chemotherapy-naïve patients undergoing high-dose cisplatin (≥70 mg/m 2 ), were given NEPA and DEX (12 mg) on day 1 and randomized (1:1:1 ratio) to receive either (a) no further DEX (DEX1), (b) oral DEX (4 mg daily) on days 2–3 (DEX3), or (c) DEX (4 mg twice daily) on days 2–4 (DEX4). The primary efficacy endpoint was complete response (CR: no emesis and no rescue medication) during the 5-day overall phase. The noninferiority margin was set at −15% difference (DEX1 or DEX3 minus DEX4). Secondary efficacy endpoints included complete protection (CP: CR and none or mild nausea). Results: Two-hundred twenty-eight patients, 76 in each arm, were assessable. Noninferiority was met for both DEX-sparing regimens and the reference arm, with overall phase CR rates of 76.3% in each of the DEX1 and DEX3 arms and 75.0% in the DEX4 arm (95% confidence interval, −12.3% to 15% for each comparison). During the overall phase, CP rates were similar between groups. Conclusion: A simplified regimen of NEPA plus single-dose DEX offers comparable chemotherapy-induced nausea and vomiting prevention throughout 5 days post-chemotherapy with the advantage of sparing patients additional doses of DEX in the high–emetic-risk setting of cisplatin-based chemotherapy. Implications for Practice: Dexamethasone (DEX) has traditionally played an integral role in the management of chemotherapy-induced emesis. Although generally considered safe, even short-term DEX use is associated with various side effects, and some evidence suggests that concurrent steroids may reduce the efficacy of immunotherapies. This study demonstrates comparable antiemetic control during the 5 days post-chemotherapy with a simplified regimen of netupitant/palonosetron plus single-dose DEX versus the standard 4-day DEX reference treatment in high-dose cisplatin. This represents a clinically relevant achievement as it not only simplifies antiemetic prophylaxis but also offers an opportunity to appropriately use in patients where caution with corticosteroid use is advised. Abstract : This study was designed to test whether two different dexamethasone-sparing regimens, when administered with NEPA, might provide the opportunity to reduce the total corticosteroid dose while maintaining the same degree of chemotherapy-induced nausea and vomiting control in patients undergoing cisplatin-based chemotherapy.